2009
DOI: 10.1143/apex.2.071404
|View full text |Cite
|
Sign up to set email alerts
|

Ge/GeO2Interface Control with High-Pressure Oxidation for Improving Electrical Characteristics

Abstract: High-pressure oxidation (HPO) of germanium (Ge) for improving electrical properties of Ge/GeO 2 stacks was investigated. The capacitance-voltage (C-V ) characteristics of metal/GeO 2 /Ge capacitors fabricated with HPO revealed improved electrical properties without any post-deposition annealing, and the interface states density (D it ) was reduced to 2 Â 10 11 eV À1 cm À2 near the midgap. Moreover, the refractive index of thermally oxidized GeO 2 was increased by HPO. It is also discussed from a thermodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
115
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 11 publications
3
115
2
Order By: Relevance
“…25,27,43,44 This result clearly indicates that the Ge(100)-2 × 1 surface is quite inert toward oxidation by pure oxygen gas unlike the case of Si oxides. The results obtained in this study seem to be considerably different from the reported results for high pressure 11 and atmospheric oxidation, 14 where the Ge 4+ state was clearly identified. Since the present results suggest that Ge 4+ cannot be formed by the reaction of pure oxygen gas at room temperature, it is likely that several processes play a role in progressing oxidation in the other methods.…”
Section: +contrasting
confidence: 99%
See 3 more Smart Citations
“…25,27,43,44 This result clearly indicates that the Ge(100)-2 × 1 surface is quite inert toward oxidation by pure oxygen gas unlike the case of Si oxides. The results obtained in this study seem to be considerably different from the reported results for high pressure 11 and atmospheric oxidation, 14 where the Ge 4+ state was clearly identified. Since the present results suggest that Ge 4+ cannot be formed by the reaction of pure oxygen gas at room temperature, it is likely that several processes play a role in progressing oxidation in the other methods.…”
Section: +contrasting
confidence: 99%
“…Since the present results suggest that Ge 4+ cannot be formed by the reaction of pure oxygen gas at room temperature, it is likely that several processes play a role in progressing oxidation in the other methods. 11,14 One possible reason for the production of Ge oxides with high oxidation states is that oxygen diffusion into oxides is dominant at high temperature. 46 This oxygen transport mechanism involved in the thermal Ge oxidation may facilitate oxidation and prevent GeO desorption relevant to GeO 2 decomposition.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, theoretical studies showed that a low interface defect (Ge dangling bond) was obtained for the GeO 2 /Ge interface due to its viscoelastic properties, 5,6 and some experimental studies demonstrated good electrical properties of the Ge-MOS. [7][8][9][10] For example, Hosoi et al reported that the electrical properties of Ge-MOS capacitors could be improved by in situ vacuum annealing at 300 C prior to metal gate electrode deposition, and an increase in the inversion capacitance, depending on its air exposure time, could be suppressed by an Al 2 O 3 layer capped on the GeO 2 surface. 8 Meanwhile, Kutsuki et al reported that surface nitridation on ultrathin GeO 2 was an effective way to improve the electrical properties (drastic suppression of leakage current, etc.)…”
mentioning
confidence: 99%